IMPLEMENTASI MODEL PEMBELAJARAN GUIDED INQUIRY PADA MATA PELAJARAN IPAS SISWA KELAS V SEKOLAH DASAR NEGERI 02 LEMPONG KECAMATAN JENAWI KABUPATEN KARANGANYAR TAHUN AJARAN 2024/2025 - Karisma Yogi Utomo; Dwi Anggraeni Siwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to describe the implementation of the Guided Inquiry Learning Model in the Science subject of fifth-grade students at SDN 02 Lempong, Jenawi District, Karanganyar Regency, in the 2024/2025 academic year. This research method is descriptive with a qualitative approach. The subjects were one principal, one teacher, and one student at SDN 02 Lempong, Jenawi District, Karanganyar Regency. Data collection methods used in this study included interviews and documentation. Data analysis techniques used in this study included data reduction, data display, and conclusion drawing. The results indicate that the guided inquiry model was implemented through six core stages: problem orientation, problem identification and formulation, hypothesis formulation, data collection and processing, conclusions, and communication of results, with active teacher guidance. Implementation of this model has been shown to increase student engagement, critical thinking skills, and scientific skills. Furthermore, this approach also positively impacted students' understanding of the concept of environmental change and increased awareness of environmental sustainability.